The Role of Government & Its Relation to Macro Economic Policy.: Examining the Effectiveness of Fiscal and Monetary Policies on Economic Growth in Nigeria (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The paper examined the relative effectiveness of fiscal and monetary policy instruments on economic growth sustainability in Nigeria in order to determine the appropriate mix of both policies. The paper employed error correction mechanism whereby the time series properties of fiscal and monetary variables were first examined using Augmented Dickey-Fuller and Philip Perron unit root tests, followed by Johansen cointegration test among the series using annual data for the period 1970-2013. Data were sourced mainly from Statistical Bulletin published by the Central Bank Nigeria. The unit root test results revealed that all fiscal and monetary policy variables are non-stationary and attained stationarity at first difference. The result also showed that all the fiscal and monetary variables of interest cointegrated with the economic growth series in the country. This suggests that there is a long run relationship among fiscal and monetary variables and economic growth. The paper, however, found that the current level of exchange rate and its immediate past level, domestic interest rate, current level of government revenue and current level of money supply are the appropriate policy instrument mix in promoting economic growth both in the short and long run. The paper concluded that fiscal and monetary are still complementary.